Modelling invasive alien plant distribution: A literature review of concepts and bibliometric analysis. (November 2021) - Dutra Silva, Lara; Bento Elias, Rui; Silva, Luís
Abstract: In the last decades, the number of publications dedicated to the application of species distribution models (SDMs) to invasive alien plants (IAPs) has constantly increased. Although recent reviews have addressed very relevant issues in the application of SDMs, the modelling approaches (i.e., algorithms) applied to IAPs have not been systematized. Therefore, we undertook a bibliographic review of articles devoted to SDMs and IAPs, from 1996 to 2019. Our results indicate that maximum entropy, generalized linear models, boosted regression trees and random forest were the four most frequent types of modelling approaches. It was clear that there was a variety of different approaches, regarding the type of algorithm to be used. We discuss the characteristics of the most cited algorithms, providing examples of their application in SDMs dedicated to IAPs. We advocate the use of a combination of different algorithms, an intensive evaluation of predictors, a thorough validation process, and a critical analysis of model predictions. Highlights: In the last 25 years, the interest in species distribution models applied to invasive alien plants raised considerably. From 1996 to 2019 we identified 526 articles addressing 17 main types of modelling algorithms. There was a tendency for an increase along time in the diversity of applied algorithms. We discuss the advantages and limitations of the different approaches and suggest general guidelines.